“HOW MUCH INDONESIAN CAN I USE?” EXPLORING PRE-SERVICE TEACHERS’ TRANSLANGUAGING EXPERIENCE IN EFL CLASSROOMS - Annisa Rahmadani; Susan Santika; Nida Mujahidah Fathimah; Siti Nurhasanah; RTS Alfira Khairunnisa (The Journal of English Literacy Education: The Teaching and Learning of English as A Foreign Language, 2025)
Translanguaging has received growing attention in multilingual EFL contexts, yet little is known about how pre-service teachers enact this pedagogy after formal exposure in university coursework. This study examined how pre-service EFL teachers enacted translanguaging during teaching practicum and what factors shaped their pedagogical decisions. Drawing on six pre-service English teachers from a public university in Indonesia, the study traced participants’ practicum enactment following a Speaking for Academic Purposes course that introduced translanguaging principles through pedagogical modelling and guided reflection. Data were generated through semi-structured interviews (approximately 15-30 minutes each; ≈100 minutes in total) and analyzed using reflexive thematic analysis (Braun & Clarke, 2023). Findings indicate that translanguaging serves cognitive functions; scaffolding comprehension through planned movement between English and Indonesian and guiding learners back to English for academic expression, affective functions; reducing anxiety, boosting confidence, and supporting participation, and identity-related functions; affirming students’ linguistic repertoires, including local languages, to foster inclusive classroom spaces. However, translanguaging enactment was negotiated within the confines of institutional English-medium expectations, mentor influence, and concerns about balancing English exposure with strategic L1 use. The findings inform EFL teacher education by highlighting the need for explicit, practicum-oriented translanguaging preparation, mentor development that validates principled multilingual pedagogy, and clearer EMI guidance that legitimizes strategic translanguaging in multilingual classrooms.